The role of mobile learning in improving 21st century teacher competencies: A systematic literature review - Sinaga, Muhammad Najmi Alwi; Kuswandi, Dedi; Fadhli, Muhibuddin (Universitas Negeri Yogyakarta, 2024)
The current learning process has entered the 21st-century era, requiring teachers to possess digital learning technology competencies in the teaching and learning process. The 21st-century teacher competencies are known as TPaCK or Technological, Pedagogical, Content Knowledge, which involves integrating technology in designing teaching materials, delivering content, and teaching students. One of the current hot trends in learning, especially in Indonesia, is mobile-based learning or Mobile Learning. The TPaCK framework and mobile-based learning share the similarity of requiring technological learning competencies. Therefore, this research aims to examine efforts to enhance 21st-century teacher competencies using Mobile Learning. The main contribution of this research is to provide empirical evidence on the effectiveness of Mobile Learning in improving teachers' technological competencies. This research serves as an important reference for educators and policymakers in designing strategies for improving teacher competencies based on digital technology. The method used in this research is a Systematic Review with the PRISMA framework. The research results indicate that the implementation of Mobile Learning can create various mobile-based learning media, enabling teachers to enhance their competencies. Moreover, the findings highlight the significant role of Educational Technologists in facilitating learning and improving performance.